397 Effect of Smartamine M on acute phase protein response in receiving beef heifers. (5th December 2019) - Grant, Madeline S; Speer, Hannah F; Hollenbeck, William R; Wahl, Ross N; Luchini, N D; Blasi, Dale A; Titgemeyer, Evan C
Abstract: Methionine supplementation can improve immune function in transition dairy cattle. Our objective was to determine if supplemental methionine could reduce acute phase protein responses in newly received growing cattle. 384 crossbred heifers (222 kg initial BW; southeastern U.S. origin) were received in 4 truckloads (blocks) over 9 d. BW was measured at arrival. The following day (d 0) cattle were vaccinated for viral and clostridial diseases, received Draxxin (2.5 mg tulathromycin/kg BW), and were stratified within block by arrival BW to 1 of 8 pens containing 12 animals each. Cattle (in 32 total pens) were limit-fed at 2.2% of BW daily (DM basis) a ration containing 40% Sweet Bran, 34.5% dry-rolled corn, 10% corn silage, 7.5% supplement, 4% alfalfa hay, and 4% prairie hay. Within blocks, pens were assigned to 1 of 2 treatments: 0 (control) or 10 g/d Smartamine M (SM) to provide 6 g/d metabolizable methionine. Pen weights were collected weekly to adjust feed offered the following week. Individual BW and tail-vein blood samples were collected on d 0, 14, and 45. Plasma haptoglobin was measured to assess acute phase protein response. Incidences of morbidity (1.6% for control, 2.6% for SM) and mortality (0.5% for both control and SM) were low. Between d 0 and 45, no differences were observed for ADG (1.24 vs. 1.27 kg/d; control vs. SM, P = 0.55) or G:F (0.107 vs. 0.110, P = 0.28), but DMI was 1.3% greater (P < 0.01) for control than SM due to differences in diet DM. An interaction between treatment and linear effect of day was detected for plasma haptoglobin (P < 0.05); over time, haptoglobin increased more for control (2.15, 2.28, and 2.95 mg/mL at 0, 14, and 45 d) than for SM (2.35, 2.37, and 2.58 mg/mL). Supplemental methionine may alleviate acute phase protein responses in stressed receiving cattle.